Stable and unstable cosmological models in bimetric massive gravity - Könnig, Frank; Amendola, Luca (Arxiv, 2014)
Nonlinear, ghost-free massive gravity has two tensor fields; when both are dynamical, the mass of the graviton can lead to cosmic acceleration that agrees with background data, even in the absence of a cosmological constant. Here the question of the stability of linear perturbations in this bimetric theory is examined. Instabilities are presented for several classes of models, and simple criteria for the cosmological stability of massive bigravity are derived. In this way, we identify a particular self-accelerating bigravity model, infinite-branch bigravity (IBB), which exhibits both viable background evolution and stable linear perturbations. We discuss the modified gravity parameters for IBB, which do not reduce to the standard $Λ$CDM result at early times, and compute the combined likelihood from measured growth data and type Ia supernovae. IBB predicts a present matter density $Ω_{m0}=0.18$ and an equation of state $w(z)=-0.79+0.21z/(1+z)$. The growth rate of structure is well-approximated at late times by